Camel country: Assemblage, belonging and scale in invasive species geographies. (January 2015) - Gibbs, Leah; Atchison, Jennifer; Macfarlane, Ingereth
Highlights: Environmental management must move beyond a native/alien species dichotomy. Focus on impacts creates a management impasse; we disrupt the impacts discourse. Assemblage thinking reveals agency beyond individual species. Species management should take into account relations across multiple scales. We must be open to futures that include living with invasive species. Abstract: Invasive species and their impacts have become a focus of global environmental management. Invasive, alien and feral species are understood to represent destructive categories of organisms. However, in the context of contemporary environmental change and uncertainty, the native/alien dichotomy is no longer tenable as the basis for decision-making, and the focus on impacts presents an impasse in environmental management. The differential status of camels ( Camelus dromedarius ) over time and space illustrates the complexity of species management. In this paper we seek to move beyond the native/alien dichotomy, and disrupt the discourse of impacts, through an analysis of camel assemblages in Australia. We draw on assemblage thinking to critique the circumstances under which camels are deemed to belong, or not, and to reveal aspects of the camel story often ignored in its contemporary telling. We present three case studies: first, an historical case of the introduction of camels to Australia; second, camel management through a national-scale culling program; and third, relations between camels and 'weeds' in which camels are deemed simultaneously to belong and not belong. We argue that assemblage thinking disrupts fixed categories, and reveals agency beyond that of individual species, thus contributing to multi-scalar considerations. We find that camel belonging does not emerge from the animal or species itself, but is contingent. Finally, we argue that camel management is currently firmly imagined and enacted at the national scale, but in the context of contemporary environmental change invasive species management must take into account processes and relations across multiple scales.